Increased production of bacST4SA by Enterococcus mundtii in an industrial-based medium with pH-control - Coetzee, Johannes Cornelius Jacobus (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2007.